RETRACTED: Galeoto et al. Assessment Capacity of the Armeo® Power: Cross-Sectional Study. Technologies 2023, 11, 125 - Giovanni Galeoto; Anna Berardi; Massimiliano Mangone; Leonardo Tufo; Martina Silvani; Jerónimo González-Bernal; Jesús Seco-Calvo (Technologies)
The Technologies Editoral Office retracts the article titled “Assessment Capacity of the Armeo® Power: Cross-Sectional Study” [...]